Effects of Gender on Emotional Intelligence in Employability Skills of Technical Education Graduate - Ibrahim H. BAKO; Yusif S. ABU; Fatima ABASHE; Muhammad NURTANTO; Abdullahi RABIU (FUDMA Journal of Engineering and Technology, 2026)
This study is conducted to determine the effects of gender on emotional intelligence in employability skills of technical education graduate in northern Nigeria. The study used descriptive research techniques using quantitative approach. The data collected for the purpose of this study was a structured questionnaire from 249 technical education students from universities in northern Nigeria that offers technical and vocational education programme. It was validated by experts in technical education.  Cronbach alpha was used to test the reliability of the developed instrument with internal reliability of 0.76 and also coefficient of 0.84. The study was conducted using one null hypothesis and was tested at 0.05 probability level for the study. The data collected was analysed using independent sample t-test. This result indicted that, the two groups male and female emotional intelligence competency of employability skills scores is not significantly different (P > 0.05). The researchers recommended that the employers of labour should not discriminate their staff based on genders difference. As the finding indicated no significant difference in favour of any of the two groups.
Keywords: Gender, Emotional Intelligence, Employability Skills, Technical Education Graduate.